Spatial variation and predictors of anemia among women of reproductive age in Mozambique, 2022/23: a multiscale geographically weighted regression - Deresse Abebe Gebrehana; Tadesse Tarik Tamir; Gebretsadik Endeshaw Molla; Yishak Kebede; Dejen Tegegne; Solomon Gedlu Nigatu; Araya Mesfin Nigatu (Frontiers in Public Health)
IntroductionAnemia is a critical global public health issue, especially among women of reproductive age (15–49 years) in low- and middle-income countries. Mozambique has the highest prevalence of anemia in women of reproductive age in Sub Saharan Africa in 2019. This study aims to assess the spatial variation and predictors of anemia among women of reproductive age in Mozambique.MethodsIndividual record and spatial coordinates data from the Mozambique Demographic and Health Survey (DHS 2022/23) were used. A stratified two-stage cluster sampling method was applied. Global autocorrelation analysis was performed to determine clustering of anemia. A weighted sample of 5,907 women of reproductive age was analyzed using ArcGIS 10.7. Multiscale geographically weighted regression was employed to identify predictors of anemia.ResultsThe national prevalence of anemia among women of reproductive age in Mozambique was 51.89% (95% CI: 50.66, 53.12%). Higher rates were observed in Nampula, Zambezia, and Sofala. Unimproved drinking water, pregnancy, and being underweight were positively correlated with anemia, while contraceptive use and obesity were negatively correlated. Geographic variability in these associations was evident (Global Moran’s I = 0.0.444359 and p < 0.001). Anemia was the highest in Tete and Manica due to unimproved drinking water the effect of pregnancy on anemia was significant in Manica and Sofala. Being underweight was strongly related to anemia in Niassa. Conversely, contraceptive use and obesity had a protective effect in Nampula, Zambezia, Niassa, and Cabo Delgado.ConclusionAnemia remains a critical public health issue among women of reproductive age in Mozambique, with marked regional disparities. Hotspot clusters were identified in Nampula, Zambezia, Tete, and Sofala. Factors such as unimproved drinking water, pregnancy, and being underweight were associated with higher anemia rates in certain regions, while obesity and contraceptive use indicated a protective effect in specific provinces. To effectively combat anemia, policymakers should focus on improving access to clean water and maternal health services, and enhancing nutritional support through the USAID Advancing Nutrition Project, the Global Alliance for Improved Nutrition, Integrated Community Case Management, and Supervised Weekly Iron and Folic Acid Supplementation.